Taxation and rotation age under stochastic forest stand value - Luis H. R. Alvarez; Erkki Koskela (Center for Economic Studies and ifo Institute (CESifo), 2004)
The paper uses both the single rotation and ongoing rotation framework to study the impact of yield tax, lump-sum tax, cash flow tax and tax on interest rate earnings on the privately optimal rotation period when forest value growth is stochastic and forest owners are either risk neutral or risk averse. In the case of risk-neutral forest owner higher yield tax raises the optimal harvesting threshold and thereby prolongs the expected rotation period. The same qualitative result holds for lump-sum tax and for the tax on interest rate earnings, while the cash flow tax is neutral. Under risk aversion the optimal harvesting threshold is lower and the expected rotation period shorter than under risk neutrality both in the single and ongoing rotation cases. Comparative statics of taxes are similar as under risk neutrality with the exception of cash flow tax, which may not be neutral anymore. Numerical results indicate that the optimal harvesting threshold both as a function of the yield tax and the forest value volatility increases more rapidly under risk neutrality than under risk aversion.
Keywords: C44; D80; Q23; 330; optimal rotation; taxation; stochastic forest value; risk aversion; Forstökonomie; Forststeuer; Steuerwirkung; Abholzung; Theorie